“Determinación de carbapenemasas KPC y OXA-48, que fenotípicamente pertenecen al grupo de las serincarbapenemasas, en cultivos de Escherichia coli y Klebsiella pneumoniae, mayo – julio, Trujillo 2018” - Guevara Peralta, Gladys Esther (2019)
ABSTRACT Infections by beta-lactamase producing bacteria are a serious problem in our country, so there has been a progressive increase in the frequency of infections caused by these bacteria, especially Escherichia coli and Klebsiella pneumoniae, due to poor compliance to therapy prescribed antibiotic or the high frequency of self-medication. The major threat is represented by carbapenemase-producing enterobacteria, potent enzymes that inactivate carbapenemic antibiotics and, in general, all beta-lactam antibiotics. The objective of this research was to determine carbapenemases KPC and OXA-48 in 73 E. coli cultures and 27 cultures of K. pneumoniae obtained from the Regional Docente Hospital of Trujillo, during the months of May to July. 2018. It was determined from the total of enterobacteria crops evaluated, 20% correspond to ESBL-producing enterobacteria, of which 17.8% corresponds to Escherichia coli and 25.9% to Klebsiella pneumoniae, in addition to 13.7% of E. coli and 7.4% of K. pneumoniae are producers of carbapenemases. However, no crops that are within the group of sericarbapenemasas have been obtained. In addition, also the frequency of carbapenemase KPC and OXA-48 was 0% in both E. coli cultures and K. pneumoniae cultures.